Pengaruh Program Pembelajaran Terstruktur terhadap Pengetahuan dan Keterampilan dalam Penggunaan Skala Visual Infusion Phlebitis (VIP) pada Perawat di RSUD Arosuka - Yosdedrison Yosdedrison; Yulastri Arif; Dorisnita Dorisnita; Susmiati Susmiati; Zifriyanthi Zifriyanthi; Elmi Elmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The Visual Infusion Phlebitis (VIP) scale is used to assess early signs of phlebitis. The number of phlebitis in Arosuka Hospital still exceeds the standard set at 1‰. This VIP scale training and socialization has not yet been given to nurses. This research aims to find out the influence of structured learning programs on the knowledge and skills of nurses in using the Visual infusion phlebitis (VIP) scale. Quasy eksperiment research type, posttest design–only non equivalent control group. The sample number of 66 respondents consisted of 33 intervention group respondents and 33 control group respondents with purposive sampling techniques. The results of the study averaged the knowledge of nurses intervention group 14, with a value range of 11-15, and the average control group of nurse knowledge 13, with a range of values 5-15. Average nurse skills in intervention group 8 with a range of grades 7-8, and the average control group nurse skills 7 with a range of grades 6-8. The results of the Mann-Whitney test showed a significant difference in the knowledge of nurses between the intervention group and the control group, p value = 0.022. There was a significant difference in the skills of nurses between the intervention group and the control group, p value = 0.001. It can be concluded that structured learning programs effectively improve the knowledge and skills of nurses in the use of VIP scales.. It is expected that there is the creation of SOP on the follow up sheet of infusion therapy.